2018
DOI: 10.1111/ijpp.12452
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve medication adherence among Chinese patients with hypertension: a systematic review and meta-analysis of randomized controlled trails

Abstract: Objective A systematic review and meta-analysis of randomized controlled trials (RCTs) were performed to understand the effectiveness of medication adherence (MA) interventions among Chinese patients with hypertension. Methods A literature search was conducted with three English databases (PubMed, Web of Science and Embase) and three Chinese databases (China National Knowledge Infrastructure, Wanfang and VIP Database for Chinese Technical Periodicals) for the period from 1970 to October 2017. Only both RCTs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Multisectoral intervention to tackle sedentary lifestyles, obesity and diabetes, which are prevalent in both settings [ 45 ], should also be developed. A recent systematic review reveals several efficacious intervention programmes for improving the adherence to medication by hypertension patients in China [ 46 ]. The role of gender and the needs for developing gender-specific blood pressure guidelines should be studied further [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multisectoral intervention to tackle sedentary lifestyles, obesity and diabetes, which are prevalent in both settings [ 45 ], should also be developed. A recent systematic review reveals several efficacious intervention programmes for improving the adherence to medication by hypertension patients in China [ 46 ]. The role of gender and the needs for developing gender-specific blood pressure guidelines should be studied further [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of using supportive method on BP control in the 12-month study of da Silva et al was similar to the subgroup analysis of the 6-month studies in this review. The study was unable to demonstrate that a longer period of intervention would produce a larger effect on adherence behavior [47]. Regardless of the whole study period, combined education might not produce a better effect on BP control than single education.…”
Section: Delivery Modementioning
confidence: 81%
“…Second, the evaluative studies do point to some potentially promising measures. However, all should be subject to further evaluation and there is a clear need for much more research on interventions that have been found to be promising elsewhere [5658].…”
Section: Discussionmentioning
confidence: 99%